Urgensi analisis berbasis bukti dalam indeks kualitas kebijakan emergency call 112 Kota Probolinggo - Siti Marwiyah; Ach. Noor Busthomi; Nurul Jannah Lailatul Fitria (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
The quality policy requires evidence-based research so that quality and pro-public policies are in the form of community services. This includes the emergency call policy for 112 Probolinggo City as stated in the Mayor's Regulation Number 175 of 2019 concerning Amendments to Mayor's Regulation Number 155 of 2018 concerning the Implementation of Services for the 112 City of Probolinggo Emergency Call Number. This study was conducted to determine the urgency of evidence-based analysis related to the quality index of the Emergency Call 112 policy in Probolinggo City. This research is qualitative research by applying a descriptive approach. Sources of data are collected from sources and direct observations accompanied by documents such as books, scientific journals, and scientific and popular articles as supporting references. Evidence-based policy analysis is a variety of techniques and methods for generating policy-related data and information. Urgency Evidence-based policy analysis is the basis for the importance of carrying out the analysis. The reason is that evidence-based policies can be used as material in the Policy Quality Index. Not only as an indicator of policy quality, but can assist in determining future decisions with the evidence, data, and information needed. The five points of the study include program assessment, program development, implementation of supervision, monitoring results, and targeted evaluations. All of these five things require evidence in the Emergency Call 112 service in Probolinggo City.